Two-way knowledge transfer in nineteenth century China : the Scottish missionary-sinologist Alexander Wylie (1815-1887) - Gow, Ian. (Abingdon, Oxon : Routledge, 2023)
This book is a biography of a remarkable Scottish missionary worker, Alexander Wylie, a classical nineteenth century artisan and autodidact with a gift and passion for languages and mathematics. He made significant contributions to knowledge transfer, both to and from China: in missionary work as a printer, playing an important role in the production and distribution of a new Chinese translation of the Bible; as a teacher, translating into Chinese key western texts in science and mathematics including Newton and Euclid and publishing the first Chinese textbooks on modern symbolic algebra, calculus and astronomy; and as a writer in English and an internationally recognised major sinologist, bringing to the West much knowledge of China and contributing extensively to the development of British sinology. The book concludes with an overall evaluation of Wylie's contribution to knowledge transfer to and from China, noting the imbalance between the significant corpus of scholarly work specifically on Wylie by Chinese scholars in Chinese and the lack of academic studies by western scholars in English.
Keywords: Wylie, A. -- 1815-1887; Missionaries -- Scotland -- Biography; Missionaries -- China -- Biography; Missions -- China; SOCIAL SCIENCE / Ethnic Studies / General; SOCIAL SCIENCE / Research